Before the Arginusae: popular participation and the control of magistrates at the dawn of the Greek polis (Circe de clásicos y modernos, 2025)
The Arginusae Trial, in which the Athenian assembly tried and sentenced its ten generals to death during the Peloponnesian War, is often considered an exceptional event and even a deviation of the radical democracy. However, a review of archaic sources and heroic poetry demonstrates that this behavior is firmly rooted in a long tradition of popular control whose  origins date back to the dawn of the polis and whose earliest expressions we find in various passages of the Iliad and the Odyssey.
Keywords: Euthýna; archaic polis; Homer; assembly; magistrates